THE NEED FOR THE CORRECT SELECTION OF THE COLOR OF HOSPITAL CLOTHING FOR PATIENTS WITH SKIN DISEASES - Arabbaeva Firyuza Uchkunovna (Journals Park Publishing, 2024)
The article deals with the issues of the need for the correct selection of the color of hospital clothes for patients with skin diseases.
Keywords: colors clinic, hospital, hospital, special clothing, skin diseases, research results, active colors, passive colors, psychological impact, physiological impact.